2016
DOI: 10.7306/gq.1338
|View full text |Cite
|
Sign up to set email alerts
|

Organic-matter vitrinite reflectance variability in the Outer Carpathians, Poland: relationship to tectonic evolution

Abstract: Zieliñska, M., 2017. Or ganic-mat ter vitrinite reflectance vari abil ity in the Outer Carpathians, Po land: re la tion ship to tec tonic evo lu tion. Geo log i cal Quar terly, 61 (1): 214-226, doi: 10.7306/gq.1338 Ran dom vitrinite reflectance of allochthonous plant ma te rial var ies through out all the flysch sed i men tary units of the Outer West ern Carpathians. The vitrinite reflectance of coalified phytogenic mat ter is vari able even within the same lithostratigraphic unit. There is no clear re la t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…These data are cor re lated with sed i men tary pro cesses and bi otic events re flect ing en vi ron mental cri ses dur ing the Paleogene. Changes in the di ver sity and num ber of foraminifera ob served by the au thors are re ported with re spect to both other microfossils (radio lar ians, di a toms, algae) and geo chem i cal data that are part of ar chived and published stud ies Gucwa, 1977, 1980;Muszyñski et al, 1979;Gucwa and OEl¹czka, 1980;Olszewska, 1984Olszewska, , 1985Gucwa, 1990;Gucwa and Poprawa, 1996;Dziubiñska and Narêbski, 2004;Bieñkowska-Wasiluk, 2010;Zieliñska, 2010Zieliñska, , 2017Garecka, 2012;Uchman, 2012, 2013;Szyd³o and Olszewska, 2012;OEl¹czka et al, 2014;Dziadzio et al, 2016). The re sults com piled by au thors are pre sented against the geo chron ol ogy and the strati graphic po si tion of the stud ied de pos its (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These data are cor re lated with sed i men tary pro cesses and bi otic events re flect ing en vi ron mental cri ses dur ing the Paleogene. Changes in the di ver sity and num ber of foraminifera ob served by the au thors are re ported with re spect to both other microfossils (radio lar ians, di a toms, algae) and geo chem i cal data that are part of ar chived and published stud ies Gucwa, 1977, 1980;Muszyñski et al, 1979;Gucwa and OEl¹czka, 1980;Olszewska, 1984Olszewska, , 1985Gucwa, 1990;Gucwa and Poprawa, 1996;Dziubiñska and Narêbski, 2004;Bieñkowska-Wasiluk, 2010;Zieliñska, 2010Zieliñska, , 2017Garecka, 2012;Uchman, 2012, 2013;Szyd³o and Olszewska, 2012;OEl¹czka et al, 2014;Dziadzio et al, 2016). The re sults com piled by au thors are pre sented against the geo chron ol ogy and the strati graphic po si tion of the stud ied de pos its (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…4). Or ganic de bris also ac cu mu lated in mudstones and mudstone-sandy se ries of the Istebna For ma tion (Zieliñska, 2010(Zieliñska, , 2017. This abun dant and usu ally dis persed ma te rial of ter res trial or i gin co-ex ists with very rare dinocysts in sam ples from the vi cin ity of Kamesznica (Szyd³o et al, 2015a, b).…”
Section: Paleocenementioning
confidence: 99%
“…The elevated values of this index, up to 0.75, are observed in oils accumulated in Dukla nappe and are connected with their increased maturity (Peters et al 1990). The Carpathian fine-grained rocks (especially Oligocene Menilite and Krosno beds) often contain allochthonous, reworked organic material (Zielińska 2017;Waliczek et al 2019) from eroded Pennsylvanian-age rocks. These particles' contribution to the organic matter mass is variable and decreases with total organic carbon content (Zielińska et al 2020).…”
Section: Originmentioning
confidence: 99%
“…TOM is wide spread in vary ing amounts in most Carpathian sed i ment and it rep re sents OM co eval with the Carpathian host ing sed i ments. TOM is char ac ter ized by a rich in vitrinite and inertinite macerals com po si tion and a lack of any de tri tal struc ture in di cat ing car bon iza tion of vas cu lar plants dur ing diagenesis and catagenesis of the Carpathian sed i ments (Zieliñska, 2017). Ad di tion ally, the pres ence of inertodetrinite in di cates strongly al tered or de graded plant ma te rial de rived to the sed i men tary ba sin.…”
Section: Organic-matter Sourcesmentioning
confidence: 99%
“…Thus, Turnau (1970) suggested that these two ar eas formed one Precarpathian Coal Ba sin. In con trast, thin ho mo ge neous vitrain coal-form ing lenses and lay ers in clastic sed i ments re flect car bon iza tion of ter res trial or ganic par ti cles in the Outer Carpathian flysch ba sin (Zieliñska, 2017).…”
Section: Introductionmentioning
confidence: 99%